Evaluation of the impact of calorie labeling on McDonald's restaurant menus: a natural experiment - Joshua Petimar; Maricelle Ramirez; Sheryl L. Rifas-Shiman; Stephanie Linakis; Jewel Mullen; Christina A. Roberto; Jason P. Block (BMC, 2019)
Abstract Background The long-term effect of calorie labeling on fast-food purchases is unclear. McDonald's voluntarily labeled its menus with calories in 2012, providing an opportunity to evaluate this initiative on purchases. Methods From 2010 to 2014, we collected receipts from and administered questionnaires to 2971 adults, 2164 adolescents, and 447 parents/guardians of school-age children during repeated visits to 82 restaurants, including McDonald's and five control chains that did not label menus over the study period in four New England cities. In 2018, we analyzed the data by using difference-in-differences analyses to estimate associations of calorie labeling with calories purchased (actual and estimated) and predicted probability of noticing calorie information on menus. Results Calorie labeling at McDonald's was not associated with changes in calories purchased in adults (change = − 19 cal pre- vs. post-labeling at McDonald's compared to control chains, 95% CI: − 112, 75), adolescents (change = − 49 cal, 95% CI: − 136, 38), or children (change = 13 cal, 95% CI: − 108, 135). Calorie labeling generally increased the predicted probability of noticing calorie information, but did not improve estimation of calories purchased. Conclusions Calorie labeling at McDonald's was not associated with changes in calories purchased in adults, adolescents, or children. Although participants were more likely to notice calories on menus post-labeling, there was no improvement in ability to accurately estimate calories purchased.